A Missional Church Strategy in an Era of Humanlike Chatbots - Hirome, David (Ecclesial Futures, 2024)
The recent prominence of advanced chatbots that greatly mimic human intelligence and conversation appears to have set a new stage in the rapidly developing field of Artificial Intelligence. Chatbots such as ChatGTP and Bard have risen to global popularity among internet users who interface with the chatbots in a nearly humanlike manner through a question-and-answer format. But such great technological developments also give rise to questions regarding theology and spirituality. Thus, this paper asks: what does it mean to be human in an increasingly AI driven world? How can Christian communities around the globe respond to the ongoing developments in the field of AI? Basing on missional anthropology, this paper argues for an understanding of humans as embodied agents of God as central in a missional strategy to respond to the proliferation of advanced AI chatbots today.